Efektivitas Media Tebak Gambar Terhadap Keterampilan Berbicara Pada Siswa Kelas IV SD - Utami, Monanda (Global Action and Education for Society, 2025)
Guess the picture media is a learning media that contains puzzles given as entertainment where someone is asked to guess as many words, phrases, or sentences as possible that are hinted at in the picture. The purpose of this study was to determine the effectiveness of using guess the picture media on speaking skills in grade IV students of SDN 98 Palembang. The method used in this study used the quasi-experimental method Pre-Test and Post-Test with Non-Equivalent Control-Group Design. Purposive sampling was used for sampling. This study consisted of two classes, namely class IV. A and IV. B totaling 58 students. Hypothesis testing of research data using independent sample t-test with the criteria that Ha is accepted if t_count> t_table. Obtained with a value of (t_count) 7.373> (t_table.) 1.672 and sig. (2 tailed) = 0.000 < 0.05, so the calculation shows that Ha is accepted and Ho is rejected or the hypothesis is proven that there is effectiveness of picture guessing media on the speaking skills of class IV students at SDN 98 Palembang.